Academic Integrity and Artificial Intelligence in Higher Education Contexts: A Rapid Scoping Review Protocol - Moya, Beatriz; Eaton, Sarah Elaine; Pethrick, Helen; Hayden, K. Alix; Brennan, Robert; Wiens, Jason; McDermott, Brenda; Lesage, Jonathan (Canadian Perspectives on Academic Integrity, 2023)
This paper presents a protocol with methodological considerations for a rapid scoping review on academic integrity and artificial intelligence in higher education. This protocol follows Joanna Brigg Institute’s (JBI) updated manual for scoping reviews and the Preferred Reporting Items for Systematic reviews Meta-Analysis (PRISMA) reporting standards. This rapid scoping review aims to identify the breadth of the literature reflecting the intersection of academic integrity and artificial intelligence in higher education institutions. The included studies in the review will be analyzed for insight concerning this emerging area, particularly its ethical implications. Our findings will be relevant for academic staff, administration, and leadership in higher education and academic integrity researchers.